Zmeny svalové síly a anaerobní a aerobní výkonnosti v prubehu osmitýdenniho kondicního tréninku profesionálního hokejisty : kazuistická studie - Psotta, R.; Kundrátek, M.; Lehnert, M.; Svoboda, Z.; Sigmund, M. (Czech Kinanthropology, 2012)
The aim of the case study was to analyze the effects of the 8-week fitness off-ice training in the 21 year-old professional ice hockey player. The training was preferentially focused on explosive strength and strength-endurance in major body segments, completed by the exercises for stimulation of the anaerobic and aerobic performance. Before, after 4 weeks and at the end of the training program (the 1st, 2nd and 3rd tests session, TS), the player was tested on: a) body composition (Bodystat); b) muscle strength - pull-up test, push-up test on a parallel bar, vertical squat jump (Kistler), back isometric dynamometry (Takei), knee isokinetic dynamometry (Isomed); c) anaerobic power and capacity - RAST test; d) maximal aerobic power - the 2 km running test. A significance of the changes in the performance variables during the training were tested according to the 95% confidence interval. Dynamic strength of the arms increased significantly in the 2nd TS while back isometric strength did until in the 3rd TS. The isokinetic dynamometry showed the larger gains in the dominant leg of the player. Sprint speed and running anaerobic capacity increased significantly as early as after 4 weeks of the training. VO2max estimated from the 2 km running time increased during all the training program (48,8, 55,5 a 57,7 ml.min-1.kg-1). The study suggested: a) The combination of different types of strength training without high resistance may result into the significant increase of strength of the arms and legs as early as after 4 weeks; b) Plyometric and anaerobic running exercises may contribute to the increase of sprint speed which is the best predictor of skating speed in the hockey players; c) The functional asymmetry of the legs in ice hockey players may be the factor of different neuromuscular adaptations to training exercises.